Implementation of a Fuzzy Logic Controlled Full Bridge SPWM Inverter for Lighting and Charging Applications - Dionova, Brainvendra; Permana, Muhammad Zidan Regi; Vresdian, Devan Junesco; Pratama, Legenda Prameswono; Jaenul, Ariep; Nugraha, Dian; Mohammed, M. N. (Jurnal Teknologi dan Manajemen, 2025)
As energy sources continue to dwindle, they have garnered significant attention, prompting the government to set a target of at least 31% of Indonesia's total energy consumption coming from renewable sources. This study focuses on developing an inverter, a device that converts direct current (DC) into alternating current (AC), utilizing a 12V/100Ah battery to support a 150-watt AC load. The proposed inverter adopts a full-bridge configuration with single-phase sinusoidal pulse width modulation (SPWM) and incorporates a fuzzy logic controller to ensure stable output voltage. The implementation results indicate that the designed full-bridge inverter produces a steady output aligned with the input from a 12V LiFePO4 battery, as confirmed by data collection which compared the output with and without control, showing that the controlled system yields a more stable output. The testing results of the full-bridge inverter using the SPWM method indicate that the system can produce an AC output voltage of 221–224 V with a frequency of 50 Hz, in accordance with the established standards. In contrast, during testing without control, the output voltage ranged only between 145–147 V with a frequency of 99.18 Hz, which does not meet operational standards. These results clearly demonstrate the effectiveness of the fuzzy controller in maintaining both voltage and frequency stability under varying operating conditions. By accurately adjusting the system response, the fuzzy controller ensures that the inverter consistently delivers output within the desired standard range, thereby enhancing the overall performance and reliability of the system.